Large-scale historic habitat loss in estuaries and its implications for commercial and recreational fin fisheries. (2nd September 2022) - Stamp, Thomas; West, Elizabeth; Robbins, Tim; Plenty, Shaun; Sheehan, Emma
Abstract: Estuaries provide important nursery and feeding habitat for numerous commercially and ecologically important fish, however, have been historically subject to substantial habitat alteration/degradation via environmental fluctuations, sea level rise, human activity on intertidal habitats, and adjacent land management. This review has summarized estuarine habitat use for 12 economically important finfish in the United Kingdom, of which seven were found to utilize estuarine habitats e.g. saltmarsh during their life cycle. This review reveals that ∼2500 km 2 of intertidal habitat has been lost from estuaries in England and Wales since 1843. The implications of this large-scale habitat loss and continued anthropogenic disturbance within estuaries for a variety of fish species is discussed, in particular the requirement of finfish for particular habitats to be accessible and in a suitable condition. As a result of the high economic and social value of commercial and recreational fisheries, it is suggested that further research attention should investigate the spatial ecology of fish. Holistic fisheries management policies should also be considered, which would both sustainably manage fisheries landings but also account for the habitat requirements of the fisheries species.